2020
DOI: 10.1200/jco.19.00510
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Single-Arm Study of Preoperative Letrozole for Estrogen Receptor–Positive Postmenopausal Ductal Carcinoma In Situ: CALGB 40903 (Alliance)

Abstract: PURPOSE Primary endocrine therapy for ductal carcinoma in situ (DCIS) as a potential alternative to surgery has been understudied. This trial explored the feasibility of a short-term course of letrozole and sought to determine whether treatment results in measurable radiographic and biologic changes in estrogen receptor (ER)–positive DCIS. PATIENTS AND METHODS A phase II single-arm multicenter cooperative-group trial was conducted in postmenopausal patients diagnosed with ER-positive DCIS without invasion. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…High-risk lesions such as atypical hyperplasia and lobular carcinoma in situ express ER and are effectively treated with either tamoxifen or aromatase inhibitors [38,39]. ER + DCIS can be treated with preoperative endocrine therapy for 6 months (Priority C) [40]. For management of ER-disease see Surgical Oncology section.…”
Section: High-risk Lesions and Pre-invasive Bcmentioning
confidence: 99%
“…High-risk lesions such as atypical hyperplasia and lobular carcinoma in situ express ER and are effectively treated with either tamoxifen or aromatase inhibitors [38,39]. ER + DCIS can be treated with preoperative endocrine therapy for 6 months (Priority C) [40]. For management of ER-disease see Surgical Oncology section.…”
Section: High-risk Lesions and Pre-invasive Bcmentioning
confidence: 99%
“…The association between pathologic upstaging and time to operation in DCIS patients has previously been studied in the NCDB, with results consistent with ours, although patients were not stratified by ER status. 2 The possible mitigating effect of NET on disease progression in ER+ DCIS has been demonstrated in a small series, 18 and was part of the recommended delay strategies during the pandemic. Although there were too few DCIS patients on NET to render an adequate analysis in the current study, taken together, these data suggest that initiation of NET in patients with ER+ DCIS is a reasonable delay strategy.…”
Section: Discussionmentioning
confidence: 99%
“…First, margin width, a crucial covariable used to support RT decisions, is not included in SEER data 10,11 . Similarly, SEER data does not include information on endocrine therapy 60,61 , though it is used as an adjuvant treatment after surgery with/without RT for DCIS [62][63][64] . We also observed that ER/PR-positive tumors treated with RT, had reduced risks of SHMs compared to counterparts with ER/PR-negative diseases.…”
Section: Discussionmentioning
confidence: 99%